Evaluation of antioxidant capacity of ethanol, acetone, ether and aqueous extract of mistletoe leaves - Khalili , Sahar; Hamidi, Yeganeh; Delfanian, Reyhaneh (Journal of Biological Studies, 2022)
Mistletoe plant is one of the medicinal plants used to treat cancer, high blood pressure, fatigue and anxiety, inflammatory diseases and regulate the immune system. The aim of this study was to evaluate the antioxidant capacity of mistletoe leaf extract in aqueous, ethanol, ether and acetone solvents. In this laboratory experimental study, mistletoe plant leaves were collected from Rudsar city in Guilan province. After extraction by succulent method, concentrations of 0.5, 0.7, 1, 1.5, 2, 2.5, 5, 7.5, 25, 50 mg/ ml were prepared. The antioxidant capacity of the extracts was measured by DPPH method. The data were analyzed using one-way ANOVA. The results showed that aqueous and ethanolic extracts had the highest and ketone and ethanolic extracts had the lowest antioxidant capacity. The antioxidant capacity significantly decreased with increasing of extract concentration. The present study showed that the aqueous extract of mistletoe had higher antioxidant capacity than ethanol, acetone, and ether extraction. Increasing the concentration of the extract not only did not increase but also reduced the antioxidant capacity. Therefore, the use of aqueous extract with proper concentration is considerably important for the therapeutic purposes.